ICT and Lifelong Learning: Hong Kong’s Experience for Elderly Learners - Lam, Sanches; Chung, Winnie (International Journal of Emerging Technologies in Learning (iJET), 2010)
Learning plays a key role in ageing societies as it can help to address many of the related challenges and opportunities. Opportunities to learn should be given to senior citizens through appropriate local lifelong learning programmes. There is a need to improve research and development on learning tools and approaches designed to meet the different needs of older people. ICT has an important role to play in developing learning opportunities for older people both as a topic in its own right and as a means of learning in the so called knowledge society. This paper reports on a Hong Kong case survey understanding the role of ICT in lifelong learning for elderly and its impact of learning activity. The survey results suggest numbers of areas should be taken into consideration for older people as both learners and mentors.